2019
DOI: 10.1021/acsnano.9b05535
|View full text |Cite
|
Sign up to set email alerts
|

Bone Biomineral Properties Vary across Human Osteonal Bone

Abstract: The biomineralization of bone remains a puzzle. During Haversian remodeling in the dense human cortical bone, osteoclasts excavate a tunnel that is then filled in by osteoblasts with layers of bone of varying fibril orientations, resulting in a lamellar motif. Such bone represents an excellent possibility to increase our understanding of bone as a material as well as bone biomineralization by studying spatio/temporal variations in the biomineral across an osteon. To this end, fluorescence computed tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 84 publications
9
26
0
Order By: Relevance
“…Notably that includes a contrast between osteon lamellae and cement lines in skeletons that were never interred in the ground as well as archaeological bones buried in soil for centuries. An uneven trace element distribution in old and recent bones in this study is consistent with what other researchers have reported for modern bones [5,6]. Taken together, these findings increase confidence that results largely free from the effects of diagenesis are possible with archaeological specimens, as long as proper precautions are followed as outlined in a study that specifically addressed that issue [1].…”
Section: Diagenesissupporting
confidence: 92%
See 1 more Smart Citation
“…Notably that includes a contrast between osteon lamellae and cement lines in skeletons that were never interred in the ground as well as archaeological bones buried in soil for centuries. An uneven trace element distribution in old and recent bones in this study is consistent with what other researchers have reported for modern bones [5,6]. Taken together, these findings increase confidence that results largely free from the effects of diagenesis are possible with archaeological specimens, as long as proper precautions are followed as outlined in a study that specifically addressed that issue [1].…”
Section: Diagenesissupporting
confidence: 92%
“…This study builds on earlier work that involved the elemental mapping of microscopic features visible in cortical bone cross-sections to identify signals attributable to diagenesis, as opposed to those reflecting life experiences, notably dietary composition and residential location [1]. These results parallel those of Swanston et al [2,3] and Choudhury et al [4] who characterized the distributions of Sr and Pb by means of synchrotron radiation in long bone cross sections from archaeological skeletons that were about two centuries old, and the work of Pemmer et al [5] and Wittig et al [6] who examined microstructural variation in trace element concentrations in modern bones. Collagen in the bone microstructure of Dutch whalers interred in Spitsbergen has likewise been investigated for stable isotopes by Koon and Tuross [7].…”
Section: Introductionsupporting
confidence: 55%
“…Spectro-microscopic XANES imaging by creating energy stacks of 2D element maps (Monico et al ., 2015) has recently been advanced to XANES tomography of virtual slices (Mijovilovich et al ., 2019). Scanning XRF can be complemented by (powder) X-ray diffraction (Vanmeert et al ., 2015; Wittig et al ., 2019) for simultaneous imaging of structure and element composition since the advent of fast hybrid pixel detectors with millisecond dwell time like the Pilatus 300k, Lambda and Eiger X 4M at P06. The small pixel size of the Eiger detector together with a large propagation distance made fast ptychographic measurements possible at the Microprobe.…”
Section: Introductionmentioning
confidence: 99%
“…orders m = [0,0,0,0] and l = [0,2,4,6] and a zenith orientation parameterized with the spherical angles q and f, that the obtained angularly averaged intensity was very comparable for each q-bin and did not change the fitted values (see SI Figure 7). This approach is comparable with conventional diffraction CT [25,[35][36][37] or small-angle scattering CT [32] in the sense that it is backprojecting the intensity as a scalar quantity to form a volume, in which every voxel contains a 1D scattering curve. All the projections recorded under all tilt angles α were used to reconstruct the volume, thus it yields the average azimuthal scattering of the 3D reciprocal-space map.…”
Section: Reconstruction Of Sastt Datamentioning
confidence: 99%